Analysis on the soil physical, chemical, and microbial community properties of different alpine meadow patches in the Source Zone of the Yellow River, West China. (November 2022) - Duan, Chengwei; Li, Xilai; Li, Chengyi; Yang, Pengnian; Shi, Yan; Chai, Yu; Xu, Wenyin
Graphical abstract: Highlights: Soil degradation has significant effects on soil physical characteristics of meadow. Meadow degradation makes soil components easily eroded by high water flow. Meadow degradation can significantly alter soil microbial community. Plateau zokors interfered-patches should be improved by no-tillage reseeding. Plateau pikas disturbed-patches should be improved by artificial recovery means. Abstract: Severe degradation of alpine meadow in the Source Zone of the Yellow River (SZYR) seriously affects the stability and sustainability of the local grassland ecosystem. Although some progress has been made in understanding the degradation process, mechanism and restoration, existing restoration technologies do not target at topographic and hydrothermal conditions, resulting in instability and poor sustainability of the restored ecosystem. This study quantified the effects of grassland degradation severity (non-degraded patch (NP), vegetated patch (VP), bare patch (BP)) on the soil physical, chemical properties and microbial community composition and their interactions in the alpine meadow in the SZYR on the Eastern Qinghai-Tibet Plateau, West China. Results showed that as the degradation severity worsens from NP to BP, soil moisture, total porosity, electrical conductivity, and root biomass decreased significantly, while soil bulk density and permeability increased significantly. The contents of soil organic carbon, total nitrogen and total phosphorus decreased significantly with the enlargement of meadow patches. There were significant differences in community structure and functional microorganisms of soil bacteria and fungi in different meadow patches. In conclusion, strategies such as replanting local grass species, adding organic fertilizer and microbial fertilizers and increasing soil compaction intensity of patches to maintain soil moisture, should be considered for restoring the degraded meadow patches.